The remnant of the midbody as a cellular signaling mechanism - Khripkov , I.S.; Golikova , A.A. (Морфологія / Morphologia / Morfologìâ, 2024)
Cell signaling mechanisms are the basis for intercellular integration and regulation of proliferation and differentiation processes at the systemic level. One of the most plausible ways to control cell-to-cell interaction and targeted distribution of genetic information is for cells to use their own structures that are formed during mitosis and carry RNA-dependent signaling molecules that affect the mechanisms of control of intercellular interaction, cell proliferation and differentiation. The midbody remnant is a microtubule-rich structure that forms between dividing cells in the last stages of cytokinesis. Previously, it was thought to be only a temporary structure of the intercellular bridge during cytokinesis, which served to connect two future daughter cells. This structure is a key regulator of abscission and functions as a signaling platform that coordinates the cytoskeleton and endosomal dynamics during the terminal stages of cell division. The midbody is a subcellular structure that is formed during cell division, during penetration into the cleavage sulcus, when the microtubules of the central spindle are compacted and cross-linked by a thin intracellular bridge connecting the two daughter cells. The midbody plays a key role in organizing cytokinesis by recruiting a variety of mitotic kinases such as Aurora B and Plk1, as well as sulcus endosomes containing Rab11/FIP3, the membrane-rupturing ESCRT complex and the microtubule-rupturing enzyme spastin, all of which are responsible for mediated rupture during the later stages of cytokinesis. The midbodies can serve as extracellular and intracellular polarity signals during early embryogenesis, as well as during epithelialization and polarization of neurons. The molecular mechanism that governs the positioning of the middle body and how it transmits signals to neurons during differentiation or epithelium remains unknown. Importantly, the remains of the middle bodies can also function as intracellular signaling scaffolds that regulate proliferation and fate postmitotic cells. Since these structures can be released outside cells and taken up by other non-mitotic cells, it is suggested that they may function as vehicles for alternative transmission of complex sets of signaling molecules and/or receptors between cells, thus profoundly affecting signaling in general.